MARIÀ VAYREDA: EL CARLISMO RECICLADO Y EL INCONSCIENTE CATALÁN - Illas, Edgar (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This essay turns on the efficacy of Kantian aesthetic categories, as explained in the «Analytic of the Beautiful» in Critique of Judgment, to determine the formation of a common sense that can configure the ideal of a coherent people. It studies the Catalan case, as the Catalans strive to form a literary canon. The novelistic essays of Vayreda, in particular La punyalada, offer a distinctive example of the working of the Kantian categories.